Leukocytoclastic vasculitis and acute renal failure after influenza vaccination in an elderly patient with myelodysplastic syndrome - Ulm, Silke; Hummel, Margit; Emig, Michael; Barreto Miranda, Manuel; Back, Walter; Reiter, Andreas; Hehlmann, Rüdiger; Willer, Andreas (Onkologie, 2006)
Influenza vaccination is recommended for individuals over 65 years of age and for all patients with chronic diseases who are at risk. Side effects which are seen in 1-10% of the vaccinated individuals are usually mild and consist of local reactions and constitutional symptoms. Since 1974, about 30 cases of vasculitis following influenza vaccination have been reported. Case Report: We here describe a 70-year-old male patient with a 5-year history of myelodysplastic syndrome, who had received continuous steroid treatment since 2004 and presented with leukocytoclastic vasculitis and acute renal failure requiring hemodialysis therapy 1 week after influenza vaccination. High-dose steroid treatment was promptly initiated, but hemodialysis was needed for 9 days. Maintained steroid treatment for 2 weeks was associated with complete recovery of renal function and skin lesions. Conclusion: As influenza vaccination is increasingly used, physicians should be aware of the potential serious side effect of leukocytoclastic vasculitis, particularly in patients who are immunocompromised either due to an underlying disorder or as a treatmentrelated side effect.